Paper from Cotton Linters as Substrate for Ammonia Nanosensor using Electrospun Alginate Nanofibers - SARAF, KOMAL; VIGNESHWARAN, N. (Cotton Research Journal, 2021)
Nanosensor to detect ammonia was produced using electrospun nanofibers of sodium alginate (SA) blended with poly (vinyl alcohol) (PVA) by adding pH indicator dyes. During electrospinning, nanofibers were collected on a cellulosic paper prepared from cotton linters, at a flow rate of 0.5 mL/h, 15 kV voltage and 15 cm spinneret tip to collector distance. The conductivity and viscosity of the solutions were measured to understand the effect of pH indicator dyes in the solutions used for electrospinning. Optical microscopy, SEM and AFM analyses were performed to evaluate the morphology of nanofiber mats. The pH indicator dye loaded nanofiber mats were characterized by UV–visible spectroscopy, dye leaching test, contact angle measurement and CIE color space analyzer. This flexible nanosensor prepared on paper substrate can find potential application in various fields like smart fish packaging, human breath analysis and agriculture as it can help to determine the nature of soil.